Analytical Solution of Laminar Forced Convection in a Heated Channel Subjected to Reciprocating Flow - Regeb, A.M.A.; Alshara, A.K.M (Basrah Journal for Engineering Sciences, 2010)
Hydrodynamics and heat transfer in a fully developed laminar incompressible reciprocating channel flow subjected to a constant heat flux have 'been investigated analytically using similarity transfo1mat ion. An exact analytical solution for the velocity, local, and bulk temperature as well as the Nusselt number has been obtained. The effect of the parameters Pr, Ao, y, and X/Dh on u, T, Tt, Nux, and Nux are presented. The results showed that the local Nusselt number is increased with increasing Womersly number (A.) while the dimensionless temperature is increased with Womersly and decreases with amplitude (Ao). The Prandtl number has a significant effect on the local Nusselt number. The results were found in very good agreement with those obtained numerically using the finite volume method. The comparison with the experimental results of other authors gave a reasonable identification.